The transcription factor Schnurri plays a dual role in mediating Dpp signaling during embryogenesis. - Torres-Vazquez, J.; Park, S.; Warrior, R.; Arora, K. (Development, 2001)
Decapentaplegic (Dpp), a homolog of vertebrate bone morphogenic protein 2/4, is crucial for embryonic patterning and cell fate specification in Drosophila. Dpp signaling triggers nuclear accumulation of the Smads Mad and Medea, which affect gene expression through two distinct mechanisms: direct activation of target genes and relief of repression by the nuclear protein Brinker (Brk). The zinc-finger transcription factor Schnurri (Shn) has been implicated as a co-factor for Mad, based on its DNA-binding ability and evidence of signaling dependent interactions between the two proteins. A key question is whether Shn contributes to both repression of brk as well as to activation of target genes. We find that during embryogenesis, brk expression is derepressed in shn mutants. However, while Mad is essential for Dpp-mediated repression of brk, the requirement for shn is stage specific. Analysis of brk; shn double mutants reveals that upregulation of brk does not account for all aspects of the shn mutant phenotype. Several Dpp target genes are expressed at intermediate levels in double mutant embryos, demonstrating that shn also provides a brk-independent positive input to gene activation. We find that Shn-mediated relief of brk repression establishes broad domains of gene activation, while the brk-independent input from Shn is crucial for defining the precise limits and levels of Dpp target gene expression in the embryo.